Strategi Guru Pendamping Khusus (Shadow Teacher) dalam Menangani Siswa ADHD di SDN Murtajih 1 Pademawu Pamekasan - Kafil Umam; Lailatus Syarifah; Lailatul Jannah; Halimatus Sa’diyah (Papanda Publisher, 2025)
This study aims to describe the strategies employed by the Special Assistant Teacher (shadow teacher) in handling students with Attention Deficit Hyperactivity Disorder (ADHD) at SDN Murtajih 1 Pademawu, Pamekasan. This research adopts a qualitative approach using data collection techniques such as direct observation and in-depth interviews with the shadow teacher, classroom teacher, and observations of the ADHD student's behavior. The findings reveal that the shadow teacher plays a vital role in creating an adaptive learning environment through various strategies, including structured instruction, positive reinforcement, emotional support, and social behavior management. These strategies are rooted in psychological and pedagogical principles that support the holistic development of the child. The implementation of such strategies has proven effective in increasing student concentration, reducing impulsive behavior, and encouraging active participation in learning activities. Moreover, the shadow teacher serves as a bridge between the ADHD student, the classroom teacher, and the social environment. Therefore, the presence of a shadow teacher is crucial in realizing inclusive education that is child-friendly and responsive to diverse learning needs